Portrait of Children's Media Literacy in Border Areas - Gushevinalti Gushevinalti; Azahar Kasim (JENTIK : Jurnal Pendidikan Teknologi Informasi dan Komunikasi, 2024)
This research aims to explore the digital literacy activities of students in border areas in Bengkulu. This research will be conducted in elementary schools in two border areas in the city of Bengkulu, namely State Elementary School 13 Babatan Seluma Regency and State Elementary School 54 Tanjung Sakti in Central Bengkulu Regency. Meanwhile, the respondents and informants of this study were elementary school students in grades 5 and 6. The selection of the research site was considered because the school's location was far from the city centre of Bengkulu and was on the outskirts of the border area. The research phase carried out is the identification of media impact problems among elementary school children (especially in schools that are the object of research), a Survey of consumption patterns, media access, media habits, and media utilization among elementary school children (at school and home); The literature review covers aspects of the elementary school curriculum and alternative development, and a literature study of the principles of media literacy applied to learning at the elementary school level. The results also showed that the questionnaire of this study was divided into five parts, namely introduction, self-identity, media behaviour, children's activities on social media and closing. Data captured in the answers of students or respondents illustrates that media activities, both audio-visual and digital, are very high in access. This is supported by their many opportunities for access to both media. In addition, parental supervision tends to be weak in controlling children's media behaviour.